OPTIMASI KENDALI KECEPATAN MOTOR DC PADA KEADAAN TRANSIEN MENGGUNAKAN PENGENDALI PID BERBASIS POLINOMIAL ITAE - , HARRY CHRISTANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
DC motors have been widely use in industry, especially in drive systems. One of the main parameters in drive system is speed. Commonly use controller for speed control is PID controller tuned according to the Ziegler Nichols method, however, it produces high percent overshoot dan control signal that cause saturation in the actuator and abrupt change in starting current of DC motor at the transient state and the DC motor will be broken. Therefore, the aim of this research is to design a method to determine the parameters of PID in order to have step response with minimum overshoot, settling time, and control signal at the transient state. In this research, the closed loop system consists of controllers and plant. The controllers are PID and I-PD controller, and the plant is a DC motor module ES151 Feedback. The closed loop system is modeled into state space form by using PID output feedback method in order to obtain the matrix of the closed loop system. The characteristic polynomial of the closed loop system is approached with the modified ITAE polynomials. These ITAE polynomials is added with a first order system in order to reduce the overshoot of the step response. The proposed methods are compared with Ziegler Nichols based PID controller and transient specification performance based PID controller. In simulation and experiment results of DC motor speed control in condition without load or disturbance, ITAE polynomial based PID controller with l = 0,85 has sufficient performance at the transient state. In condition with load, ITAE polynomial based PID controller with l = 0,95 has sufficient performance at the transient state, however, in condition with disturbance, Ziegler Nichols has good disturbance rejection compared to other controllers. ITAE polynomial based I-PD has sufficient speed performance, but its energy tends to high. Thus, ITAE polynomial based PID controller has sufficient performance at the transient state compared to other controllers. Keywords: DC Motor, PID, I-PD, Ziegler Nichols, PID Output Feedback, ITAE Polynomials